Content Determination of Active Component in Huangqi Yinyanghuo Group and Its Effects on hTERT and Bcl-2 Protein in Osteosarcoma - Ying Tan; Lei Tan; Shuai Huang; Junfan Lu; Longtan Yu (Journal of Analytical Methods in Chemistry)
To screen the optimal extraction process and content determination of active component of Huangqi Yinyanghuo group (HYG) and to study the effects of HYG on human telomerase reverse transcriptase (hTERT) and Bcl-2 protein in osteosarcoma (HOS) cells, providing the theoretical basis for clinical application of HYG in treatment of osteosarcoma, orthogonal design table L9(43) was used to design the extraction process of HYG, and icariin was taken as the investigation index to optimize the extraction process of HYG. 0.125, 0.25, 0.5, 1, 2, 4, and 8 μmol/L HYG were taken to act separately on logarithmic growth phase osteosarcoma HOS cells, CCK-8 assay was used to determine cell viability, and immunohistochemical SP assay was used to determine the expression of hTERT and Bcl-2 protein. Apoptosis rate was positively correlated with the dose of HYG, and the expressions of hTERT and Bcl-2 protein were significantly decreased with the prolonged duration of action. Under the effect of HYG, dose was negatively correlated with osteosarcoma cell survival fraction; osteosarcoma cell survival fraction was positively correlated with hTERT and Bcl-2 protein; duration of action was negatively correlated with hTERT and Bcl-2 protein; and hTERT and Bcl-2 protein were in a synchronous relationship.